Intranasal Oxytocin for Stimulant Use Disorder Among Male Veterans Enrolled in an Opioid Treatment Program: A Randomized Controlled Trial - Stauffer, Christopher S.; Samson, Salem; Hickok, Alex; Hoffman, William F.; Batki, Steven L. (Frontiers in Psychiatry, 2022)
The increasing prevalence of illicit stimulant use among those in opioid treatment programs poses a significant risk to public health, stimulant users have the lowest rate of retention and poorest outcomes among those in addiction treatment, and current treatment options are limited. Oxytocin administration has shown promise in reducing addiction-related behavior and enhancing salience to social cues. We conducted a randomized, double-blind, placebo-controlled clinical trial of intranasal oxytocin administered twice daily for six weeks to male Veterans with stimulant use disorder who were also receiving opioid agonist therapy and counseling (n=42). There was no significant effect of oxytocin on stimulant use, stimulant craving, or therapeutic alliance over six weeks. However, participants receiving oxytocin (versus placebo) attended significantly more daily opioid agonist therapy dispensing visits. This replicated previous work suggesting that oxytocin may enhance treatment engagement among individuals with stimulant and opioid use disorders, which would address a significant barrier to effective care.